(In reply to Solution
Let the ages of each after 15 years of marriage of the man and his wife be respectively M and N
Hence, from the fundamental tenets governing the puzzle, we obtain:
(i) M = 2N; (ii) (M - 15) = 3(N - 15)
So, substituting M= 2N in (ii), we obtain:
2N - 15 = 3(N-15) giving: N = 30 so that: M = 30*2 = 60
[EDIT] Consequently, subtracting 15 from the each of the values of M and N thus obtained, we observe that at the time of the marriage, the respective ages of the man and his wife were respectively 45 and 15.
Edited on June 28, 2007, 11:40 am